(untitled) (Journal of Parents and Teachers, 2014)
The issue of communication between adults and adolescents is dealt by means of four brief daily situations in which adolescents show their emotional needs and insecurities. The practical activities help the reflection of how this communication is produced and how it can be led, and their possible alternatives.